Catechins-Modified Selenium-Doped Hydroxyapatite Nanomaterials for Improved Osteosarcoma Therapy Through Generation of Reactive Oxygen Species - Khan, Suliman; Ullah, Muhammad Wajid; Siddique, Rabeea; Liu, Yang; Ullah, Ismat; Xue, Mengzhou; Yang, Guang; Hou, Hongwei (Frontiers in Oncology, 2019)
Currently, the selenium-doped hydroxyapatite (Se-HAp) nanoparticles have received immense therapeutic and tissue repairing values owing to their antitumor activities. However, a high concentration of Se is toxic towards normal and stem cells whereas its low concentration cannot effectively remove the cancer cells. Therefore, the current study was aimed to improve the anticancer activity of Se-HAp nanoparticles through catechins (CC) modification owing to their high cancer therapeutic value. The sequentially developed catechins modified Se-HAp nanocomposites (CC/Se-HAp) were characterized for various physicochemical properties and antitumor activity. Structural analysis showed the synthesis of hexagonal needle-like single phase HAp nanoparticles with length ranging from 50-100 nm with an average width of 15 nm. Fourier transform infrared (FTIR) spectroscopy showed the successful synthesis of HAp nanoparticles and their interaction with the Se and catechins. Field-emission scanning electron microscopy (FE-SEM) showed the Se-HAp agglomerated structures and impregnation of catechins. Cell toxicity analysis showed that catechins modification improved the antitumor activity of Se-HAp nanocomposites against the human osteosarcoma HOS/MNG cell lines without affecting the growth of human normal bone marrow stem cells (hBMSCs). TEM analysis showed the internalization and degradation of CC/Se-HAp nanomaterials within the MNNG/HOS cells through a non-specific endocytosis process. The current study of combining natural biomaterial (i.e. catechins) with synthetic drugs (i.e. Se and HAp) to improve the treatment outcome and preventing the adverse and toxic effects towards the normal cells can prove to be an effective therapeutic approach for bone cancer therapy.